The influence of lower limb muscle activity on postural stabilisation during landing in female artistic gymnasts - Pavlasová, K.; Bizovská, L.; Rupcik, L.; Farana, R.; Janura, M. (Sports Biomechanics, 2026)
The aim of this study was to assess the influence of lower limb muscle activity and postural stabilisation during landings after various motor tasks. Seventeen gymnasts (aged 13.7 ± 2.0 years) performed landings after four tasks: drop landing, forward somersault, backward somersault, backward acrobatic series. Postural stabilisation during landing was assessed using an inertial sensor placed on the lumbar spine, from which data was used to determine the dynamic stability index and time to stabilisation. Muscle activity was assessed using surface electromyography in six lower limb muscles. The results showed that the muscle activity of the lower limbs differs according to the difficulty and direction of the motor task preceding the landing. The activity of the knee flexors and plantar flexors during landing after forward and backward motor tasks proved to be more beneficial for improving postural stabilisation. The study shows the importance of balanced muscle activation of the hip, knee and ankle flexors and extensors during landing, especially for injury prevention and effective execution of difficult gymnastic landings.